Parametric Evaluations of the Rogers-Ramanujan Continued Fraction - Nikos Bagis (International Journal of Mathematics and Mathematical Sciences)
In this paper with the help of the inverse function of the singular moduli we evaluate the Rogers-Ranmanujan continued fraction and its first derivative.